The syringe sampler: An inexpensive alternative borehole sampling technique for CO2-rich fluids during mineral carbon storage - Alfredsson, H.; Mesfin, K.; Wolff-Boenisch, Domenik (2015)
Mineral carbon storage involves the dissolution of injected gaseous or supercritical CO2 followed by interaction of the carbonated solution with the host rock at depth resulting in the precipitation of carbonate minerals. Monitoring of elemental chemistry and tracers is required to evaluate the evolution of the fluid geochemistry and the degree of CO2 mineralization during its injection into the subsurface. To avoid degassing during sampling, which is a common feature of commercial groundwater samplers, especially vacuum samplers, a syringe-like sampler was designed, constructed, and tested in the lab and field. This system was successfully deployed during the injection of 175 tons of pure gaseous CO2 at the CarbFix injection site in Hellisheidi, SW Iceland. This study presents in detail this sampling tool and its application to the monitoring of the CO2-rich fluid evolution during subsurface carbonation. The syringe sampler was developed as a flexible and mobile unit of low investment and operating costs making it an attractive option for deployment at small scale carbon storage demonstration sites that do not command the budgets to deploy commercial alternatives, e.g. from the oil and gas industry.